Dynamic modeling and control of nonholonomic wheeled mobile robot: when subjected to wheel slip - Sidek, Shahrul Na'im; Sarkar, Nilanjan (VDM Verlag, 2009)
Improving navigation performance of autonomous wheeled mobile robot (WMR) in a dynamic unstructured environment requires improved maneuverability. In such cases, the dynamics of wheel slip may violate the ideal no-slip kinematic constraints generally used to model nonholonomic WMR. In this dissertation, a new model is proposed to tackle the modeling inadequacy that arises when slip is neglected by including both longitudinal and lateral slip dynamics into the overall dynamics of the WMR. The presented model of the WMR provides a realistic simulation scenario that can be utilized to develop model-based controllers to improve WMR navigation. In particular, to demonstrate how this model can be useful in developing modelbased planning and control of WMR with wheel slip, a dynamic path-following controller is designed to allow the WMR to navigate efficiently by autonomously regulate its forward velocity based on the generated traction force at the wheel-surface contact point. Extensive simulation results show the importance of the proposed modeling technique to capture slip phenomenon and the efficacy of the presented control technique to exploit such slip for better navigation performance. In addition, through experiments, the dynamics of slip in the system model has beenb verified.